Haemophagocytic Lymphohistiocytosis with Leptospirosis: A Rare but Devastating Complication. (8th July 2021) - Munasinghe, B. M.; Arambepola, A. G.; Pathirage, N.; Fernando, U. P. M.; Subramaniam, N.; Nimalan, S.; Gajanthan, T.
Abstract : Introduction . Secondary haemophagocytic lymphohistiocytosis (sHLH), often associated with an array of infections, malignancies, and autoimmune diseases, is rarely seen with leptospirosis, which carries a relatively poor prognosis even with modern state-of-the-art medical care. We describe a patient with leptospirosis complicated by sHLH who succumbed to illness following multiorgan dysfunction. Case Description . A 74-year-old farmer presented with high-grade, unsettling fever for a week. Muddy water exposure and suggestive symptoms prompted investigation and management in the line of leptospirosis (IV ceftriaxone was instituted, and later, MAT (microscopic agglutination test) became positive). Subsequently, he developed severe acute hypoxemia requiring mechanical ventilation and acute renal failure requiring renal replacement therapy. Bone marrow biopsy and markedly elevated serum ferritin and triglyceride levels done on day 10 (with unresolving fever, hepatosplenomegaly, and pancytopaenia) confirmed the diagnosis of HLH. The routine cultures, retroviral studies, CMV, dengue, hanta and mycoplasma antibodies, tuberculosis and COVID-19 PCR, and malaria screening were all normal. There was no improvement of hypoxemia following intravenous methylprednisolone. He died on day 15 despite escalating organ support. Conclusion . Leptospirosis is a common zoonotic disease in the tropics with significant morbidity and mortality. In the case of severe leptospirosis, overlapping clinical features with sHLH make the diagnosis of the latter challenging. No assessment tools are available to date to predict the risk of developing sHLH in a patient having leptospirosis. Outcome following sHLH due to leptospirosis still remains majorly ominous. A high index of suspicion and low threshold for specific investigations could possibly alter the outcome following such an occurrence.